Privativeness In Russian and Uzbek Lexical Structures: An Examination of Clothing Nomenclature - Mokhinur Nekova (Periodica Journal, 2024)
This article delves into the intricate phenomenon of privativeness within the lexical structures of the Russian and Uzbek languages, with a particular focus on the nomenclature of clothing. The research methodologically examines the etymological roots and semantic shifts that underpin the conceptualization of privativeness in these two linguistically and culturally diverse languages. By conducting a comparative analysis, the study highlights the syntactic and morphological variations that manifest in the clothing terminology of Russian and Uzbek. Furthermore, this paper elucidates the cognitive and cultural implications of these linguistic structures, providing a comprehensive understanding of how privativeness operates within the broader context of lexical semantics. The findings underscore the significance of crosslinguistic studies in uncovering the nuanced interplay between language, culture, and cognition, thereby contributing to the theoretical framework of comparative linguistics and semantic theory.
Keywords: privativeness; lexical structures; Russian language